2016
DOI: 10.1080/17445647.2016.1203830
|View full text |Cite
|
Sign up to set email alerts
|

Historical ponds of the Czech Republic: an example of the interpretation of historic maps

Abstract: The paper presents a map of historical ponds of the whole Czech Republic which was created on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 30 publications
(26 reference statements)
0
37
0
7
Order By: Relevance
“…It would require complete access to the layer of place names in the database GEONAMES, combined with the vectorised layer of fishponds of all the old maps that were used. Such a layer only exists for the 2 nd Military Survey for the Czech Republic (Pavelková et al, 2016), although our research has demonstrated the importance of surveying an historical landscape, especially for the 1st Military Survey. Its more precise processing in GIS could, however, be difficult with respect to the absence of geodetic data (Demek et al, 2008;Petrovszki and Mészáros, 2010).…”
Section: Discussion Of the Methods Used In This Studymentioning
confidence: 87%
See 2 more Smart Citations
“…It would require complete access to the layer of place names in the database GEONAMES, combined with the vectorised layer of fishponds of all the old maps that were used. Such a layer only exists for the 2 nd Military Survey for the Czech Republic (Pavelková et al, 2016), although our research has demonstrated the importance of surveying an historical landscape, especially for the 1st Military Survey. Its more precise processing in GIS could, however, be difficult with respect to the absence of geodetic data (Demek et al, 2008;Petrovszki and Mészáros, 2010).…”
Section: Discussion Of the Methods Used In This Studymentioning
confidence: 87%
“…The Czech Republic was selected as the area of interest for this study. Its history of pond construction is long and ponds were widely spread here and became an important landscape phenomenon, mainly since the 1450s (Pavelková et al, 2016;Semotanová, 2009). Similar to other countries, Czech ponds fulfilled various roles, most of all as places to keep fish.…”
Section: Geographical Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The highest surface area of potentially suitable localities for the construction of retention reservoirs and wetlands was found in the region of Jihočeský (350 km 2 ). Historically, this region is a place of numerous fish ponds and artificial reservoirs (Pavelková et al, 2017). In the region of Vysočina, this surface area is 266 km 2 , in the Plzeňský region 223 km 2 , in Středočeský 176 km 2 (green colour in Fig.…”
Section: Priority Localities For Initiation Of Land Consolidations Aimentioning
confidence: 99%
“…Besides big dams, small water reservoirs spread in the landscape are intended to be a part of complex approach to increase water retention in the landscape. The reason is, among other things, the loss of these water bodies in the past [6,7]. The proper function of these structures which are listed as an important landscape element in the Act on the conservation of nature and landscape [8] is highly dependent on the hydrological regime.…”
Section: Introductionmentioning
confidence: 99%